2019
DOI: 10.3390/ijerph16173114
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prices on Youth Cigarette Smoking and Tobacco Use Initiation in Ghana and Nigeria

Abstract: Background: Population growth in the African region is set to outpace the rate of decline in smoking prevalence, leading to a projected increase in the total number of smokers. As most tobacco users initiate during their adolescent years, tobacco prevention strategies targeting youth will be particularly important. Methods: This study estimated the impact of cigarette prices on youth cigarette smoking and tobacco use initiation in Ghana and Nigeria using the Global Youth Tobacco Survey data. First, we used cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(53 citation statements)
references
References 15 publications
(16 reference statements)
5
45
0
Order By: Relevance
“…The results show that tobacco is a normal good and that growing income makes it more affordable. This finding is in tandem with previous studies that found rising incomes to influence tobacco consumption positively [ 9 , 15 ]. Given the continent’s (Africa) impressive growth performance for some time now, the current smoking prevalence in Africa is unlikely to fall substantially, if efforts are not bolstered.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results show that tobacco is a normal good and that growing income makes it more affordable. This finding is in tandem with previous studies that found rising incomes to influence tobacco consumption positively [ 9 , 15 ]. Given the continent’s (Africa) impressive growth performance for some time now, the current smoking prevalence in Africa is unlikely to fall substantially, if efforts are not bolstered.…”
Section: Discussionsupporting
confidence: 90%
“…Whether the strategy of using tax and price measures to curb smoking yields the desired results, is an empirical question that has received considerable attention in the literature [7][8][9][10][11][12][13][14][15][16]. Among these studies, only Ho et al [11] conducted a cross-country analysis for Africa, and found cigarette prices to decrease cigarette consumption.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, strict enforcement of regulations prohibiting sales of tobacco products to minors has been shown to contribute to a reduction of smoking among youths [45]. Research evidence has also shown that higher cigarette prices has decreased tobacco use onset among youths in Ghana and Nigeria [46], and this is reflected in the global literature as well. Based on these findings, the prices of cigarettes should be increased to deter youths from initiating tobacco use.…”
Section: Discussionmentioning
confidence: 99%
“…The WHO estimated that there are 2 billion alcohol users, 1.3 billion tobacco users, and 185 million illicitdrug users worldwide [2]. Currently, 80% of tobacco users live in low-and middle-income countries (LMICs) [3] and also, 80% of tobaccorelated deaths are predicted to occur in LMIC by 2030 [4]. Smoking and alcohol abuse attributable to 20% of tuberculosis (TB) disease worldwide and collectively made India a home of world's 27% of TB patients in 2017 [5].…”
Section: Introductionmentioning
confidence: 99%